2004
DOI: 10.1023/b:brea.0000018411.89667.0d
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for an Association of Human Papillomavirus and Breast Carcinomas

Abstract: Human papillomavirus (HPV) DNA has been detected in breast carcinoma by different laboratorial techniques, suggesting the virus could play a role in the pathogenesis of this tumor. The aim of the present study is to investigate the presence of HPV in patients with breast carcinoma and the correlation of the viral infection with prognostic factors for the disease outcome. Between June 2001 and July 2002, 101 paraffin embedded breast carcinoma specimens were analyzed through polymerase chain reaction (PCR) and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
132
7
4

Year Published

2004
2004
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(159 citation statements)
references
References 18 publications
16
132
7
4
Order By: Relevance
“…There were no differences in the average of age of women with either HPV-positive and -negative breast cancer in a study of Brazilian women (Damin et al, 2004). This is in contrast to a recent study of Greek women in which those with HPV-positive breast cancer were of average age 38 years as compared to average age 53 years for women with HPV-negative breast cancer (P-values for difference ¼ 0.001) (Kroupis et al, 2006).…”
Section: Sircontrasting
confidence: 63%
“…There were no differences in the average of age of women with either HPV-positive and -negative breast cancer in a study of Brazilian women (Damin et al, 2004). This is in contrast to a recent study of Greek women in which those with HPV-positive breast cancer were of average age 38 years as compared to average age 53 years for women with HPV-negative breast cancer (P-values for difference ¼ 0.001) (Kroupis et al, 2006).…”
Section: Sircontrasting
confidence: 63%
“…Many studies have reported the presence of HPV DNA in breast tissues, while others did not confirm the findings [1]. Damin et al found 25% of HPV positivity in 101 breast cancer tissues [14]; moreover, Kroupis et al [6] showed a 16% rate of HPV positivity in more than 100 breast cancer tissue specimens, and they suggested a correlation between infection and elevated tumour grading and proliferation index over a low ER+ expression. However, Lindel et al [26] did not support these findings.…”
Section: Discussionmentioning
confidence: 98%
“…Low or high prevalence of HPV DNA in breast cancer of women was found in several studies. HPV16 or HPV18 were preferentially found in European women, while other types, e.g., 33, were frequently found in Japanese and Chinese cohorts [6][7][8][9][10][11][12][13][14][15][16]. De Villiers et al have recently shown that a broad spectrum of mucosal and cutaneous HPV types could be found in breast specimens using several PCR-based methods [16].…”
Section: Introductionmentioning
confidence: 99%
“…Human papilloma virus 33 has been identified in breast cancer in Chinese and Japanese women (Yu et al, 1999). Human papilloma virus 11, 16 and 18 have been identified in breast cancer in US and separately in Brazilian women (Liu et al, 2001;Damin et al, 2004). No HPVs have been identified in normal breast tissues from normal women who have had cosmetic surgery.…”
mentioning
confidence: 99%